2002
DOI: 10.1038/sj.onc.1205803
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke carcinogens, DNA damage and p53 mutations in smoking-associated cancers

Abstract: It is estimated that cigarette smoking kills over 1 000 000 people each year by causing lung cancer as well as many other neoplasmas. p53 mutations are frequent in tobaccorelated cancers and the mutation load is often higher in cancers from smokers than from nonsmokers. In lung cancers, the p53 mutational patterns are different between smokers and nonsmokers with an excess of G to T transversions in smoking-associated cancers. The prevalence of G to T transversions is 30% in smokers' lung cancer but only 12% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
761
6
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 975 publications
(812 citation statements)
references
References 106 publications
31
761
6
14
Order By: Relevance
“…Furthermore, it has been found that in lung cancer cells, approximately 30% of GC to TA transversions occur at the hot spot codon 248 and 273 of TP53 gene and at codon 12, 13 or 61 of K-ras gene (Slebos et al, 1991;Husgafvel-Pursiainen et al, 1993;Westra et al, 1993;Greenblatt et al, 1994). A similar mutation spectrum has been detected in the TP53 gene of bronchial epithelial cells treated with B[a]P-7,8-diol-9,10-epoxide (Pfeifer et al, 2002). GC to TA transversions have also been found in Salmonella typhimurium strains by CSC treatment, suggesting a role of PAHs in inducing this class of mutations (DeMarini et al, 1995).…”
Section: Introductionsupporting
confidence: 64%
“…Furthermore, it has been found that in lung cancer cells, approximately 30% of GC to TA transversions occur at the hot spot codon 248 and 273 of TP53 gene and at codon 12, 13 or 61 of K-ras gene (Slebos et al, 1991;Husgafvel-Pursiainen et al, 1993;Westra et al, 1993;Greenblatt et al, 1994). A similar mutation spectrum has been detected in the TP53 gene of bronchial epithelial cells treated with B[a]P-7,8-diol-9,10-epoxide (Pfeifer et al, 2002). GC to TA transversions have also been found in Salmonella typhimurium strains by CSC treatment, suggesting a role of PAHs in inducing this class of mutations (DeMarini et al, 1995).…”
Section: Introductionsupporting
confidence: 64%
“…Previous studies also have suggested that nicotine, directly or indirectly, modulates the amount of DNA repair and/or DNA damage tolerance [30,44,46]. For example, nicotine increases the repair of plasmid DNA damaged by free radicals in the presence of whole-cell protein extracts from adult myocytes [30].…”
Section: Discussionmentioning
confidence: 98%
“…First, polycyclic aromatic hydrocarbons, carcinogenic compounds present in tobacco smoke, induce mutations in the p53 gene that are crucial for cell cycle dysregulation and carcinogenesis. 34 G to T transversions within the gene have been linked to a molecular signature of tobacco mutagens in smokingassociated lung cancers. Second, the N-nitroso compounds are another major group of chemicals found in tobacco smoke, several of which are potent animal carcinogens.…”
Section: Risk Factors Tobaccomentioning
confidence: 99%